Pemanfaatan Warisan Budaya Lokal: Situs Watu Dukun Di Desa Pagerukir Kabupaten Ponorogo Sebagai Sumber Belajar Ips - Afita Khoiru Nisa; Nastiti Mufidah; Siti Zazak Soraya (Faculty of Social Science, Universitas Negeri Padang, 2026)
The Watu Dukun Site is a historical heritage located in Pagerukir Village, Sampung District, Ponorogo Regency. This study aims to explore the meaning of students’ experiences in utilizing the Watu Dukun Site as a learning resource for Social Studies. This research employs a qualitative phenomenological method. The subjects of this study include Social Studies teachers and students of SMP Negeri 2 Sampung, as well as the caretaker of the Watu Dukun Site. Data were collected through interviews, observations, and documentation. Data analysis was carried out using triangulation. The findings reveal that the utilization of the Watu Dukun Site in Social Studies learning provides students with direct and authentic learning experiences through observation, the introduction of historical values, and the preservation of local culture. Learning activities at the site enhance students’ learning interest, strengthen their critical thinking skills, and foster appreciation for regional cultural heritage. In addition, teachers’ involvement in developing outdoor learning-based instruction at the site contributes to the creation of an active and enjoyable learning atmosphere.